Wave Phenomena in Helicon Plasma - Virko, V.F.; Kirichenko, G.S.; Shamrai, K.P. (Вопросы атомной науки и техники, 2003)
Employing of the electrodeless, low-pressure inductive discharges (ICPs) is preferable in many applications. A helicon discharge, which is known as the most efficient magnetized ICP [1], operates with excitation of electromagnetic helicon waves (whistlers) obeying the dispersion relation w=wcek₂kc²/w²pe where wpe and wce are the electron plasma and cyclotron frequencies, and k = (k₂²+k₁²)¹/² is the total wave number. In a radially bounded plasma, the wave fields vary as exp[i(kzz-wt-mq)] where m is the azimuthal wavenumber. Helicons are excited by external rf antennas of various designs and propagate into plasma giving rise to various wave phenomena that considerably affect the discharge operation. Some of these phenomena are examined below experimentally and theoretically.